Implementation of Islamic Religious Education Learning in Inclusive Schools in Indonesia - Nurul Iman; Mokmin Basri; Muh. Tajab; Anip Dwi Saputro; Devid Dwi Erwahyudin; Muhammad Dzikky Firman Syah (Scientia Publica Media, 2025)
The basic principles of inclusive education that values differences and promotes equality are very much in line with Islamic values that encourage respect for humanity, patience, and compassion for others. However, in practice, teaching Islamic Religious Education (PAI) in inclusive schools requires significant adjustments, both in curriculum preparation and in material delivery. Teachers are not only required to understand religious teachings in depth, but also need to have adaptive pedagogical skills, so that they can convey religious concepts, such as the pillars of faith, the pillars of Islam, or the stories of the prophets, in a way that can be understood by students with various limitations. Islamic Religious Education learning in the context of inclusive schools presents its own challenges for teachers, especially in dealing with students with special needs who have diverse abilities and learning styles. This study explores various strategies used by teachers in teaching Islamic Religious Education in an inclusive environment, including differentiation methods, curriculum adaptation, and collaboration between teachers, parents, and support staff. The results show that the success of Islamic Religious Education learning in inclusive schools is highly dependent on the ability of teachers to adapt learning methods to the needs of each student, as well as support from the school and family environment. The findings highlight the need for continuous professional development programs to enhance teachers’ adaptive pedagogical skills in inclusive education settings. It is recommended that schools strengthen collaboration with families and support staff to create a more inclusive learning environment for Islamic Religious Education.